2008
DOI: 10.1002/pc.20757
|View full text |Cite
|
Sign up to set email alerts
|

Modified continuous carbon fiber‐reinforced poly(phthalazinone ether sulfone ketone) composites by blending polyetherimide and polyethersulfone

Abstract: Poly(phthalazinone ether sulfone ketone) (PPESK) is a novel high performance thermoplastic with outstanding high temperature resistance and excellent mechanical properties and therefore, it is a very ideal candidate matrix for advanced composites. However, its high melting viscosity makes the melting process difficult. In this article, two well-known high performance thermoplastics, polyetherimide (PEI) and polyethersulfone (PES) were introduced to PPESK in order to reduce the melting viscosity of PPESK and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Recently, continuous carbon fiber (CF)‐reinforced high performance thermoplastic composites have been one of the most attractive materials for high‐performance application with the advantages of unlimited shelf‐life, recyclability, cost‐effective processing, and excellent toughness compared to those thermoset composites . Various thermoplastic matrices such as poly(ether ether ketone), poly (phenylene sulfide sulfone), polyether imide, and poly(phthalazinone ether ketone) (PPEK) have been explored to evolve demanding needs in composites with high thermal stability and excellent mechanical properties .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, continuous carbon fiber (CF)‐reinforced high performance thermoplastic composites have been one of the most attractive materials for high‐performance application with the advantages of unlimited shelf‐life, recyclability, cost‐effective processing, and excellent toughness compared to those thermoset composites . Various thermoplastic matrices such as poly(ether ether ketone), poly (phenylene sulfide sulfone), polyether imide, and poly(phthalazinone ether ketone) (PPEK) have been explored to evolve demanding needs in composites with high thermal stability and excellent mechanical properties .…”
Section: Introductionmentioning
confidence: 99%
“…At present, continuous fiber-reinforced high-performance thermoplastic composites are one of the most attractive materials for high-performance applications where high temperature stability and damage resistance are required. 1 The thermal and mechanical properties of the composites depend on the mechanical properties of fibers, and the matrix resin's thermal stability and mechanical properties. In order to fully utilize the stiffness and strength of the reinforcement fibers, it is necessary to bring the thermoplastic matrix and the reinforcement fibers together with homogeneous wetting.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the strength, modulus, hardness and wear resistance, the elongation at break, and hardness of the PPS/PTFE composites were improved by introducing 15 vol.% of CF compared with the unreinforced blend matrix. Different composites based on polymer blends have been carried out by Zheng et al [90], who prepared a blend of PEI/PES thermoplastics and introduced them into poly(phthalazinone ether sulfone ketone) (PPESK) polymers as a matrix and CCF as the reinforcement of PPESK/CF composites. They investigated both PPESK/PEI/CF and PPESK/PES/CF composites' mechanical properties.…”
Section: Mechanical Strength and Modulus Of Cfrtpmentioning
confidence: 99%